Crystal structure of bacteriophage T4 Spackle as determined by native SAD phasing. Issue 9 (2nd September 2020) - Shi, Ke; Kurniawan, Fredy; Banerjee, Surajit; Moeller, Nicholas H.; Aihara, Hideki
Abstract : The crystal structure of bacteriophage T4 Spackle as determined by sulfur SAD phasing reveals a monomeric protein with a helical bundle fold and a disc‐like overall shape. Spackle has an intramolecular disulfide bond and a bipolar surface‐charge distribution, which are consistent with its proposed role as a lysozyme inhibitor that functions in the Escherichia coli periplasm. Abstract : The crystal structure of a bacteriophage T4 early gene product, Spackle, was determined by native sulfur single‐wavelength anomalous diffraction (SAD) phasing using synchrotron radiation and was refined to 1.52 Å resolution. The structure shows that Spackle consists of a bundle of five α‐helices, forming a relatively flat disc‐like overall shape. Although Spackle forms a dimer in the crystal, size‐exclusion chromatography with multi‐angle light scattering shows that it is monomeric in solution. Mass spectrometry confirms that purified mature Spackle lacks the amino‐terminal signal peptide and contains an intramolecular disulfide bond, consistent with its proposed role in the periplasm of T4 phage‐infected Escherichia coli cells. The surface electrostatic potential of Spackle shows a strikingly bipolar charge distribution, suggesting a possible mode of membrane association and inhibition of the tail lysozyme activity in T4 bacteriophage superinfection exclusion.